Correction: Biocompatible graphene oxide as a folate receptor-targeting drug delivery system for the controlled release of anti-cancer drugs. Issue 22 (6th February 2015) - Zhao, Xubo; Liu, Peng
Abstract : Correction for 'Biocompatible graphene oxide as a folate receptor-targeting drug delivery system for the controlled release of anti-cancer drugs' by Xubo Zhao et al., RSC Adv., 2014, 4, 24232–24239.